Inter-network connection performance simulation - Claravall, Christine T. (1995)
Designing connections between computer networks implies the need to determine the inter-network connection which would provide suitable performance within the constraints usually set by expenses. This research aims to develop and implement a statistical performance simulation through the gathering of measures and deriving functions from these data. This simulation is limited to using two established standards, namely X.25 and ATM. Factors such as the speed and cost are given emphasis throughout the research due to its importance in construction of connections between networks. This research is supported by a program implementation which the group has created and called it Q-WAN. Might ask why Q-WAN Well, it had to do with simulation very much connected to queues. Queues are associated with WAN's order of service, serving those who are first on line or that who's needs is more urgent. Modeling wide-area network links entailed use of the graph theory and needed the knowledge of data unit overheads in order to adequately predict how much information is actually getting passed along the network, given its expected network traffic and a request distribution. The system thus designed was made to "send" out requests based on this distribution and see how long it will take until a response from the server will be detected. These figures will be continually updated in the program to give the user a high-low-value for the delays possible in the network. This research can be further improved by including existing standards other than the X.25 and the ATM. Another recommendation is to use more appropriate distribution models for the simulation since one model is not enough to provide a reliable prediction.